Penyelenggaraan Pemilu Yang Bersih dan Demokratis Menurut Perspektif Hukum Tata Negara Pada Pemilihan Umum Anggota Legislatif Tahun 2024 - Ronaldo Jhon Christiano Blegur; Rafael Rape Tupen; Hernimus Ratu Udju (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The principle of democracy and justice in general election (electoral justice) is that community involvement is absolute. General elections are a means of people’s sovereignty which is carried out directly, generally, freely, secretly, honestly and fairly and must meet the principles as referred to in Law Number 7 of 2017 concerning elections. The main problemsin the results of this research are: (1) How to realize clean, democratic and digfinified legislative elections, from the perspective of Constitutional Law? (2) Will there be money politics in the implementation of the 2024 elections, and what is the role of Bawaslu in handling these problems?. This research is a normative legal research, supported by empirical legal research, so that the data sources used are secondary data sources, primary data sources. Secondary data sources are obtained through literature, laws, and other literature, and supported by primary data obtained from findings in the field. Data are analyzed descriptively-qualitatively. The results of this study indicate that: (1) The implementation of clean and democratic general elections according to Constitutional Law in East Nusa Tenggara uses independent independence, functional independence, personal independence, and the principle of equality. (2) The role of Bawaslu in handling political money actions in East Nusa Tenggara seems to be still very minimal due to the welfare factor of the community which is still far from good standards so that it is still very difficult to report perpetrators of political money. Suggestions: (1) The public should be more vigilant against prospective leaders who do not have a sense of responsibility by buying votes. (2) The government should be more assertive in its level of supervision so that prospective leaders who engage in political corruption (money politics) should be crossed off the list of prospective political participants.